The possible involvement of hyperpolarizing mechanisms in histamine-induced relaxation of the rat portal vein - Rossignoli, Patrícia de S. [UNESP]; Rodrigues, Andréa D.; Tinti, Thaís; Pereira, Oduvaldo C. M. [UNESP]; Ellinger, Fred; Chies, Agnaldo B. (My University, 2008)
The present study evaluated the effects of histamine 10 -2 M on longitudinal preparations of rat portal vein. It was observed that histamine 10 -2 M induced relaxation of rat portal vein preparations pre-contracted with phenylephrine 10 -4 M. On the other hand, no pharmacological effects were observed in preparations not pre-contracted. The observed histamine-induced relaxing effect was absent in preparations pre-contracted with KCl (120 mM) or in the presence of depolarizing nutritive solution. However, the histamine-induced relaxation was still present in the endothelium-removed preparations. The histamine-induced relaxation also was not prevented by astemizole (10 -6 M, 10 -5 M and 10 -4 M), cimetidine (10 -5 M, 10 -4 M and 10 -3 M) or thioperamide (10 -6 M, 10 -5 M and 10 -4 M), selective antagonists H 1, H 2 and H 3, respectively. The presence of L-NAME 10 -4 M or L-NAME 10 -4 M plus indomethacin 10 -5 M also did not prevent the histamine-induced relaxation observed in rat portal vein. Thus, the histamine-induced relaxation observed in rat portal vein appears to involve a non-endothelial hyperpolarizing mechanism independent of H 1, H 2 and H 3 receptors.
Keywords: Endothelium; Histamine; Hyperpolarizing mechanism; Portal vein; Relaxation; astemizole; enzyme inhibitor; histamine; histamine agonist; histamine H1 receptor; histamine H1 receptor antagonist; n(g) nitroarginine methyl ester; phenylephrine; potassium chloride; vasoconstrictor agent; animal; animal model; dose response; drug effect; male; physiology; portal vein; rat; vasodilatation; Wistar rat; Animals; Astemizole; Dose-Response Relationship, Drug; Enzyme Inhibitors; Histamine Agonists; Histamine H1 Antagonists, Non-Sedating; Male; Models, Animal; NG-Nitroarginine Methyl Ester; Phenylephrine; Portal Vein; Potassium Chloride; Rats; Rats, Wistar; Receptors, Histamine H1; Vasoconstrictor Agents; Vasodilation